AVALIAÇÃO DO CARBONO E ENERGIA INCORPORADOS NO CICLO DE VIDA E DO DESEMPENHO TÉRMICO DE DIFERENTES TIPOS DE ISOLAMENTO TERMOACÚSTICO PARA PAREDES DE LIGHT WOOD FRAMING - Timm, Janaine Fernanda Gaelzer; Sartori, Gabriela; Passuello, Ana; Torres, Maurício Carvalho Ayres (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Construction industry is one of the production sectors that most impacts the environment. The mitigation of these impacts can be reached through better choices in the design phase. Several studies indicate that the use and operation phases are the stages with the greatest impacts buildings life cycle and that materials choice can influence the energy consumption related to these phases. The present study aims to compare different thermal insulation options for the Light Wood Framing System (LWF), finding which one presents the highest amount of embodied energy and the highest associated CO2eq emissions. For comparison purposes, all options present the same thermal performance defined by their thermal transmittance. The results indicate that glass wool is the option with the lowest embodied energy and expanded polystyrene (EPS) present the lowest emissions per unit area (kg CO2eq m²).